Incidence of mental health conditions following pediatric hospital admissions: analysis of a national database - Daughtrey, Hannah R.; Ruiz, Monica O.; Felix, Nicole; Saynina, Olga; Sanders, Lee M.; Anand, Kanwaljeet J. S. (Frontiers in Pediatrics, 2024)
Introduction Despite increasing survival of children following hospitalization, hospitalization may increase iatrogenic risk for mental health (MH) disorders, including acute stress, post-traumatic stress, anxiety, or depression. Using a population-based retrospective cohort study, we assessed the rates of new MH diagnoses during the 12 months after hospitalization, including the moderating effects of ICU exposure. Study design/methods This was a retrospective case control study using the Truven Health Analytics insurance database. Inclusion criteria included children aged 3–21 years, insurance enrollment for >12 months before and after hospital admission. We excluded children with hospitalization 2 years prior to index hospitalization and those with prior MH diagnoses. We extracted admission type, ICD-10 codes, demographic, clinical, and service coordination variables from the database. We established age- and sex-matched cohorts of non-hospitalized children. The primary outcome was a new MH diagnosis. Multivariable regression methods examined the risk of incident MH disorder(s) between hospitalized and non-hospitalized children. Among hospitalized children, we further assessed effect modification from ICU (vs. non-ICU) stay, admission year, length of stay, medical complexity, and geographic region. Results New MH diagnoses occurred among 19,418 (7%) hospitalized children, 3,336 (8%) ICU-hospitalized children and 28,209 (5%) matched healthy controls. The most common MH diagnoses were anxiety (2.5%), depression (1.9%), and stress/trauma (2.2%) disorders. Hospitalization increased the odds of new MH diagnoses by 12.3% (OR: 1.123, 95% CI: 1.079–1.17) and ICU-hospitalization increased these odds by 63% (OR: 1.63, 95% CI: 1.483–1.79) as compared to matched, non-hospitalized children. Children with non-complex chronic diseases (OR: 2.91, 95% CI: 2.84–2.977) and complex chronic diseases (OR: 5.16, 95% CI: 5.032–5.289) had a substantially higher risk for new MH diagnoses after hospitalization compared to patients with acute illnesses. Conclusion Pediatric hospitalization is associated with higher, long-term risk of new mental health diagnoses, and ICU hospitalization further increases that risk within 12 months of the acute episode. Acute care hospitalization confers iatrogenic risks that warrant long-term mental and behavioral health follow-up.